2016
DOI: 10.5194/acp-16-161-2016
|View full text |Cite
|
Sign up to set email alerts
|

The diurnal cycle of rainfall over New Guinea in convection-permitting WRF simulations

Abstract: Abstract. In this study, we examine the diurnal cycle of rainfall over New Guinea using a series of convection-permitting numerical simulations with the Weather Research and Forecasting (WRF) model. We focus our simulations on a period of suppressed regional-scale conditions (February 2010) during which local diurnal forcings are maximised. Additionally, we focus our study on the occurrence and dynamics of offshore-propagating convective systems that contribute to the observed early-morning rainfall maximum no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
99
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 28 publications
23
99
3
Order By: Relevance
“…Neither the pattern nor the magnitude is altered meaningfully between the two simulations. These results suggest that the diurnal cycle characteristics are not sensitive to the orography over Hainan Island, although many previous studies demonstrated that the orography can play an important role in the precipitation over other islands (Sobel et al, 2011;Hassim et al, 2016;Barthlott and Kirshbaum, 2013).…”
Section: The Simulated Diurnal Cycle and The Influence Of The Orographymentioning
confidence: 57%
See 1 more Smart Citation
“…Neither the pattern nor the magnitude is altered meaningfully between the two simulations. These results suggest that the diurnal cycle characteristics are not sensitive to the orography over Hainan Island, although many previous studies demonstrated that the orography can play an important role in the precipitation over other islands (Sobel et al, 2011;Hassim et al, 2016;Barthlott and Kirshbaum, 2013).…”
Section: The Simulated Diurnal Cycle and The Influence Of The Orographymentioning
confidence: 57%
“…With CMORPH data and regional climate model simulations, Qian (2008) found that sea-breeze convergence, mountain-valley winds and cumulus merger process are the predominant reasons for the diurnal precipitation cycles, while the underrepresentation of islands and terrain results in an underestimation of precipitation. Hassim et al (2016) examined the diurnal cycle of rainfall over New Guinea with a 4 km convection-permitting WRF model. They found the importance of sea breeze in the initiation of rainfall but focused on large-scale atmospheric properties preferred by the propagation of systems offshore at night.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the wettest places on Earth, and the high latent heat release from organized convective activity in the region influences global circulation and climate via downstream Rossby wave responses (Jin and Hoskins 1995;Neale and Slingo 2003). On a diurnal time scale, precipitation forms over the islands in the afternoon as a result of a seabreeze convergence mechanism and propagates offshore overnight through the reversal of the sea breeze and coupling to gravity waves (Saito et al 2001;Mori et al 2004;Qian 2008;Love et al 2011;Hassim et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While there are known issues with TRMM in the MC region, it is unlikely that the model-observation differences are solely due to TRMM uncertainties. Wet biases from high rainfall rates in CP configurations of the MetUM, especially over high orography, are a known issue in a number of regions of the world (Birch et al 2014a;Kendon et al 2012) and also in other CP models (e.g., Hassim et al 2016), and this bias is the subject of ongoing research at the Met Office.…”
mentioning
confidence: 99%
“…According to investigations of moist convection off mountainous coasts in different geographical regions, combinations of topographic effects, diurnally induced circulations and waves, and discontinuities in surface roughness between the land and ocean probably determine the nature of coastal convection (Garrett 1980;Houze et al 1981;Grossman and Durran 1984;Liberti et al 2001;Mapes et al 2003;Colle and Yuter 2007;Hassim et al 2016;Vincent and Lane 2016). According to investigations of moist convection off mountainous coasts in different geographical regions, combinations of topographic effects, diurnally induced circulations and waves, and discontinuities in surface roughness between the land and ocean probably determine the nature of coastal convection (Garrett 1980;Houze et al 1981;Grossman and Durran 1984;Liberti et al 2001;Mapes et al 2003;Colle and Yuter 2007;Hassim et al 2016;Vincent and Lane 2016).…”
Section: Introductionmentioning
confidence: 99%